Biskupski, Mieczysław B. B., 2011. Nieznana wojna Hollywood przeciwko Polsce 1939-1945 - Mazurkiewicz, Michał (Respectus Philologicus, 2014)
BISKUPSKI, Mieczysław B. B., 2011. Nieznana wojna Hollywood przeciwko Polsce 1939-1945. Warszawa: Fijorr Publishing. pp. 390. ISBN 978-83- 89812-77-0.